Working of Section 153A of the Income Tax Act, 1961: Resolving the Conflict between the Literal Rule of Interpretation and Harmonious Construction - Jha, Srijita; Zaveri, Akshay (Christ University Law Journal, 2017)
This article ventures into the various interpretations given by the court for the execution of Section 153A of the Income Tax Act, 1961. It has forever been a conflict as to how the particular section has to be interpreted, in order to decide whether the items of regular assessment can be added back in the proceeding under section 153A, after the finalization of assessment. This article tries to decode the mixed opinions of the court with regard to whether it is the literal rule of interpretation or the rule of harmonious construction that would apply to interpret Section 153A. This issue has been dealt with by the authors by analysing the various tools of interpretation of statutes like Literal Rule of Interpretation, reading down of statute as a whole, Rule of Harmonious Construction of statute etc. and their application in various cases based on judicial dicta of the court of law. The authors, based on thorough analysis of Section 153A, based on the language of the provision and the interpretations attached to it by the Judiciary, have tried to resolve the conflict between the Literal rule of interpretation and harmonious construction.